Miss Peregrine's home for peculiar children [videorecording (Blu-Ray + DVD)] - Goldman, Jane, 1970-; Green, Eva, 1980-; Butterfield, Asa, 1997-; O'Dowd, Chris, 1980-; Janney, Allison; Everett, Rupert; Stamp, Terence; Purnell, Ella, 1996-; Dench, Judi, 1934-; Jackson, Samuel L.; Higham, Mike; Margeson, Matthew, 1980-; et al. (Twentieth Century Fox Home Entertainment LLC, 2016)
Jacob discovers clues to a mystery and stumbles upon Miss Peregrine's Home for Peculiar Children. However the mystery is deeper than he had thought, as he gets to know the residents and learn about their special powers. Jacob discovers that only his own special peculiarity can save his new friends.